Epiphyte-cover on seagrass (Zostera marina L.) leaves impedes plant performance and radial O2 loss from the below-ground tissue - Brodersen, Kasper E.; Lichtenberg, Mads; Paz, Laura-Carlota; Kühl, Michael (Frontiers in Marine Science, 2015)
The O2 budget of seagrasses is a complex interaction between several sources and sinks, which is strongly regulated by light availability and mass transfer over the diffusive boundary layer (DBL) surrounding the plant. Epiphyte growth on leaves may thus strongly affect the O2 availability of the seagrass plant and its capability to aerate its rhizosphere as a defence against plant toxins. We used electrochemical and fiber-optic microsensors to quantify the O2 flux, DBL and light microclimate around leaves with and without filamentous algal epiphytes. We also quantified the below-ground radial O2 loss from roots ( 1 mm from the root-apex) to elucidate how this below-ground oxic microzone was affected by the presence of epiphytes. Epiphyte-cover on seagrass leaves ( 21% areal cover) resulted in reduced light quality and quantity for photosynthesis, thus leading to reduced plant fitness. A 4 times thicker diffusive boundary layer around leaves with epiphyte-cover impeded gas (and nutrient) exchange with the surrounding water-column and thus the amount of O2 passively diffusing into the leaves in darkness. During light exposure of the leaves, radial oxygen loss from the below-ground tissue was 2 times higher from plants without epiphyte-cover. In contrast, no O2 was detectable at the surface of the root-cap tissue of plants with epiphyte-cover during darkness, leaving the plants more susceptible to sulphide intrusion. Epiphyte growth on seagrass leaves thus negatively affects the light climate and O2 uptake in darkness, hampering the plants performance and thereby reducing the oxidation capability of its below-ground tissue.